Prevalence and Multidrug Resistance Indices of Listeria spp. from Bovine Milk, Milk Products and Clinical Samples in and around Junagadh City, Gujarat, India - P Suthar, Alpesh; H Sindhi, Samiulla; B Kathiriya, Jaysukh; R Bhedi, Kirit; K Sharma, Arun; J Thakre, Bhupendra (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The antibiotic resistance profiles of 18 Listeria spp. (5.14%) obtained from a total of 350 (100 bovine milk, 100 milk products and 150 animal clinical) samples were evaluated using the agar disc diffusion method against 14 commonly used antibiotics in human and veterinary medicine. All 18 Listeria isolates exhibited varying levels of resistance to the tested antibiotics. Notably, resistance observed in all isolates (100%) against ampicillin, amoxyclav and oxacillin is particularly alarming, as ampicillin remains the primary drug of choice for L. monocytogenes infections, suggesting the potential emergence of multi-drug resistant (MDR) strains. Additionally, 77.77% of the isolates (14 out of 18) showed resistance to chloramphenicol and cefepime, while 55.55% (10 isolates) were resistant to gentamicin, which further underscores the reduced efficacy of commonly used antibiotics. The isolates showing resistance to three or more antibiotics were evaluated for the multiple antibiotic-resistant phenotypes (MARPs) and multiple antibiotic resistance (MAR) index. Thirteen L. monocytogenes isolates exhibited 12 MARP patterns with sistance to 7-13 antibiotics (MAR index: 0.50-0.92), while five other Listeria spp. (2 L. innocua, 0.57%; 3 L. seeligeri, 0.85%) showed 5 patterns resistant to 8-13 antibiotics with MAR index 0.35-0.71, suggesting urgent need for stringent monitoring, judicious antibiotic use, and improved food safety measures to prevent the spread of resistant Listeria strains.